BUDAYA HUKUM DALAM PENEGAKAN HAK CIPTA PEMBAJAKAN PROGRAM KOMPUTER - Manurung, Susi Marlinda; Jessica, Jessica; Sari, Elsi Kartika (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Computers initially began to develop in 1940 in the first generation. Along with the development of the computer also helped develop which was called a computer program. Computer programs are a matter that cannot be separated from the computer itself, therefore many people do piracy against these computer programs. The computer program itself is one form of copyrighted work regulated in Law No. 28 year 2014 about Copyright. But in practice there are still many people who pirate the Computer Program so that it requires a law enforcement, especially the enforcement of criminal law against piracy of computer programs.Keywords: Computer Program, Copyright, Criminal Law